Smoking and secondhand smoke exposure and carotid intima-media thickness: Baseline data from the Aidai Cohort Study in Japan - Makoto Saito; Yoshihiro Miyake; Keiko Tanaka; Chisato Nagata; Hidenori Senba; Yasuko Hasebe; Toyohisa Miyata; Takashi Higaki; Eizen Kimura; Bunzo Matsuura; Osamu Yamaguchi; Ryuichi Kawamoto (Tobacco Induced Diseases)
Introduction Epidemiological evidence regarding the relationship between smoking and secondhand smoke (SHS) exposure and carotid intima-media thickness (CIMT) has been limited in Asian populations. Employing baseline data from the Aidai Cohort Study, Japan, we evaluated the evidence in this cross-sectional study.